Analisis Rasio Profitabilitas Untuk Mengukur Kinerja Keuangan Perusahaan Sebelum Dan Selama Pandemi Covid-19 Pada PT Vienwi Karya Teknologi - Dian Fauziah; Mardiana Mardiana; Kartolo Hutabarat (UNIVERSITAS RAHARJA, 2023)
This study aims to determine the proﬁtability ratios to assess ﬁnancial performance before and during the Covid-19 pandemic at PT Vienwi Karya Teknologi. The type of research used in this research is descriptive quantitative. This research was conducted to determine the analysis of proﬁtability ratios as a tool to measure the ﬁnancial performance of PT Vienwi Karya Teknologi in the last three years of the ﬁnancial report period. The proﬁtability ratios used are Net Proﬁt Margin (NPM), Return On Equity (ROE) and Return On Assets (ROA). The research results show that the existence of the Covid-19 pandemic shows that the ﬁnancial performance of the company PT Vienwi Karya Teknologi is not good in terms of ROA, ROE and NPM. Even though it has increased in 2021, the value achieved by this proﬁtability ratio is still below the industry standard average.